Linguistic or Communicative Competence - Which Wins? - Gregory John Tylor (Journal of Modern Languages, 2017)
This paper seeks to highlight the inseparable twins,  linguistic and communicative competence, two aspects of language proficiency related respectively to the form and the content of information exchange. The paper considers the importance of learning a foreign language in a right way, and also states that linguistic competence has little meaning if it does not foster the learner's ability to communicate in a foreign language.